BISTABILITY AND LOW-ENERGY-ELECTRON TRANSFER - DIIMINE BRIDGED COBALT SEMIQUINONATE-CATECHOLATE COORDINATION POLYMERS - JUNG, OS; LEE, YA; PIERPONT, CG (ELSEVIER SCIENCE SA, 1995)
Intramolecular shifts in charge distribution have been investigated for the coordination polymers of [Co-III(N-N) (SQ)(Cat)]n/[Co-II(N-N) (SQ)2](n) tautomers (N-N=4,4'-bipyridine analogs; SQ=3,6-di-t-butyl-1,2-semiquinone: Cat = 3,6-di-t-butylcatechol). The polymers remain exclusively in the low-spin a series of intermediate species that exhibit Co-III/co(II) equilibria in the solid state. A significant bistability on temperature has been observed by monitoring the changes in magnetism and the intensity of a low energy transition (2500nm=4000cm(-1)) that appears characteristically for the Co-III tautomer.
Keywords: TRANSITION; COMPLEXES